Identification of three gene families coordinating the conversion between fructose-6-phosphate and fructose-1,6-bisphosphate in wheat - C.M. YU; Y.C. KE; K.P. ZHANG; M. YAN; H.R. JIN; Y.H. CHEN; J. ZHANG (Biologia Plantarum, 2021)
Saccharides are a direct energy source for most organisms and the primary components in grains of common wheat (Triticum aestivum L., 2n = 6x = 42, AABBDD). However, genes involved in the metabolism of primary saccharides such as glucose and fructose have not been fully characterized in wheat, which limits our understanding of how these genes influence wheat growth. In this study, genes coding ATP-dependent phosphofructokinase (PFK), fructose-1,6-bisphosphatase (FBP), and pyrophosphate-dependent fructose-6-phosphate 1-phosphotransferase (PFP), which participate in the conversion between fructose 6-phosphate (F-6-P) and fructose 1,6-bisphosphate (F-1,6-P2), were identified at the genome-wide level. A total of 24, 13, and 12 genes were found encoding TaPFK, TaFBP, and TaPFP, respectively. All predicted peptides of these genes exhibited conserved substrate-binding domain, suggesting they are active enzymes in vivo. Transcriptome data ranked the gene levels as follows: TacyFBP-1 > TacpFBP-1 > TaPFPα-2 ≈ TaPFPβ >> TaPFK-1 ≈ TaPFK-5 >> all remaining genes at different developmental stages of wheat. In the three tapfp-a, b, and d knockout lines, there was a decrease in the plant height, anther length, and thousand-grain mass, while the percentage of abnormal pollen increased compared to that of wild type cv. Huapei3 (HP3). During germination, tapfpβ-a exhibited a lower germination rate, shorter coleoptile and primary root length, and higher fructose content than HP3, tapfpβ-b, and tapfpβ-d lines. Expressions were ranked as follows: TaPFK-5 ≈ TaPFPα-2 >> TaPFPα-1 ≈ TaPFPβ > TacyFBP-1 ≈ TaPFK-7, 9 in HP3. All these genes were downregulated during the 24 - 96 h germinating process in three mutant lines. Collectively, main TaPFK, TaFBP, and TaPFP members cooperated during wheat growth, while TaPFPβ knockout decreased wheat vitality. Results from this study can aid more systematic studies of the physiological and molecular functions of TaPFK, TaFBP, and TaPFP.